Leave the browser behind: Placing discovery within the user’s workflow - Cahoy, Ellysa Stern (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
As library discovery and delivery has largely moved online, the scholarly workflow of academic researchers has become increasingly fragmented. Faculty are using a variety of software solutions to find, retrieve, organize, annotate, cite, and share information, including library resources. This article discusses the significance of situating discovery, the act of finding new information, within software central to the research workflow, such as citation management or word processing software. The current status of discovery of library resources within citation management software is outlined, along with expected future developments. Utilizing findings from two Mellon funded studies, it explores the challenges users face in managing their individual scholarly workflows, and recommends optimizations designed to mitigate information loss and increase researcher productivity.